2007
DOI: 10.1210/en.2006-0832
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Novel Genes Regulated by Chorionic Gonadotropin in Baboon Endometrium during the Window of Implantation

Abstract: Chorionic gonadotropin (CG) is an early embryo-derived signal that is known to support the corpus luteum. An in vivo baboon model was used to study the direct actions of human CG (hCG) on the endometrium, during the periimplantation period. Endometrial gene expression was analyzed using microarrays. The endometrial biopsies were taken from hCG-treated (n = 5) and control (n = 6) animals on d 10 after ovulation. Class comparison identified 61 genes whose transcript levels differed between control and hCG-treate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
107
1
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(114 citation statements)
references
References 54 publications
5
107
1
1
Order By: Relevance
“…It has been indicated that C3, mostly synthesized in the liver, is also synthesized in the uterine endometrium of various species including rats (Sundstrom et al, 1989) and humans (Sayegh et al, 1996), which is stimulated by estradiol or chorionic gonadotropin and inhibited by progesterone (Brown et al, 1990;Sherwin et al, 2007). It is suggested from the present findings that uterine C3 functions as an embryotrophic factor at earlier embryonic stages when the maternal blood sinus is not yet formed.…”
Section: Binding Of C3 To Rat Embryossupporting
confidence: 52%
“…It has been indicated that C3, mostly synthesized in the liver, is also synthesized in the uterine endometrium of various species including rats (Sundstrom et al, 1989) and humans (Sayegh et al, 1996), which is stimulated by estradiol or chorionic gonadotropin and inhibited by progesterone (Brown et al, 1990;Sherwin et al, 2007). It is suggested from the present findings that uterine C3 functions as an embryotrophic factor at earlier embryonic stages when the maternal blood sinus is not yet formed.…”
Section: Binding Of C3 To Rat Embryossupporting
confidence: 52%
“…CG has a direct luteotrophic effect on the corpus luteum, increasing its life span. Concurrently, CG also leads to alterations in morphology and endometrial gene expression by modulating the endometrium in preparation for implantation [9].…”
Section: Chorionic Gonadotropinmentioning
confidence: 99%
“…Here, the embryo produces cytokines that induce inflammatory pathways in the endometrium (Sherwin et al, 2007). A similar response to that generated by the embryo can be stimulated by scratching the uterus, or injecting oil into the tract of females primed by treatment with progesterone and estrogen (Dekel et al, 2010).…”
Section: Amhr2mentioning
confidence: 99%